Frequency‐Dependent Responses of Plasmaspheric Hiss to the Impact of an Interplanetary Shock - Haobo Fu; Chao Yue; Qianli Ma; Ning Kang; Jacob Bortnik; Qiu‐gang Zong; Xu‐zhi Zhou (Geophysical Research Letters)
Abstract Plasmaspheric hiss waves are essential for the pitch‐angle scattering and precipitation of energetic electrons and interplanetary shocks may affect these waves. We present a case study on the responses of plasmaspheric hiss after an interplanetary shock arrival on September 7, 2017. Based on the observation by RBSP‐B, the plasmaspheric hiss in different frequency ranges shows three different responses simultaneously: hiss waves with frequency below 0.08fce are weakened, waves within 0.08–0.18fce are weakened in magnetic power and modulated by the ultra‐low frequency (ULF) waves in the electric power, while waves above 0.18fce are intensified in magnetic power and modulated by the ULF waves. Further analysis suggests that the hiss waves have different sources: low‐frequency (<∼0.18fce) hiss waves are transmitted from chorus outside the plasmasphere, while high‐frequency (>∼0.18fce) hiss waves are locally amplified. Our results provide a comprehensive view of the frequency‐dependent hiss wave behavior after the impact of interplanetary shocks.